Improvement of financial resource management in territorial communities - Podplietnii, V.; Sliusar, V.; Подплєтній, В. В. (ЦНТУ, 2025)
Addressing the identified issues and implementing the proposed measures will enhance the efficiency of financial resource management within territorial communities, ultimately improving the well-being of their residents. Вирішення виявлених проблем та впровадження запропонованих заходів підвищить ефективність управління фінансовими ресурсами в територіальних громадах, що зрештою покращить добробут їхніх жителів.
Keywords: local finances; financial planning; financial forecasting; місцеві фінанси; фінансове прогназування; фінансове планування